The concept of the “pedagogical event” in educational discourse - Victoria V. Dobrova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Clarification of conceptual and terminological apparatus is an urgent task of modern pedagogy, in this connection the paper deals with the concept of pedagogical event, as well as its relationship with the main pedagogical categories: education, training and upbringing. Based on the research conducted within the social and human sciences, the integral features of the event, such as the significance of changes in the life of the subject and spatial and temporal characteristics were identified, which allowed to define the pedagogical event in an interdisciplinary dynamic aspect. One of the main functions of education in the modern world is the transmission of culture from one generation to another, reproduction and development of culture. If the aim of education is understood as the transmission, reproduction and generation of culture, the pedagogical event can be defined as a change through adaptation of cultural experience of humanity to the cultural experience of the student, i.e. translation of culture from one person to another.